2008
DOI: 10.1097/mlg.0b013e318170b5dc
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Transnasal Craniotomy and the Resection of Craniopharyngioma

Abstract: The endoscopic management of large craniopharyngioma emphasizes recent advancements in endoscopic skull base surgery. The ability to provide exposure through a large (4 cm+) transnasal craniotomy, near-field assessment of neurovascular structures, and the successful reconstruction of a large skull defect have significantly advanced the field in the past decade. The use of a two-surgeon approach and bilateral pedicled septal mucosal flaps have greatly enhanced the reliability of this approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
53
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(54 citation statements)
references
References 29 publications
1
53
0
Order By: Relevance
“…Some authors have described their own protocols for reconstruction of the sella according to the tumor extension or intraoperative findings 2,3,4,5,8 ; however, the pedicled nasoseptal flap was not included as an option in these other protocols. Since Hadad et al 9 described vascular pedicle nasoseptal flap as a novel reconstruction technique in 2006 (Hadad-Bassagasteguy flap; HBF), it has been reported that this flap can function well to separate the intradural space from the nasosinusal cavity 6,10,11,12,15 . They reported a 4.7% rate of postoperative CSF fistula in a sample of 43 patients including 20 pituitary adenomas, all of which had presented intraoperative CSF fistula and required reoperations 9 .…”
mentioning
confidence: 99%
“…Some authors have described their own protocols for reconstruction of the sella according to the tumor extension or intraoperative findings 2,3,4,5,8 ; however, the pedicled nasoseptal flap was not included as an option in these other protocols. Since Hadad et al 9 described vascular pedicle nasoseptal flap as a novel reconstruction technique in 2006 (Hadad-Bassagasteguy flap; HBF), it has been reported that this flap can function well to separate the intradural space from the nasosinusal cavity 6,10,11,12,15 . They reported a 4.7% rate of postoperative CSF fistula in a sample of 43 patients including 20 pituitary adenomas, all of which had presented intraoperative CSF fistula and required reoperations 9 .…”
mentioning
confidence: 99%
“…However, longer followup studies are needed to confirm its long-term effectiveness. [10][11][12][13][14]19,23,24,30,32,[35][36][37]40,41,57,60 implications for cP treatment strategy…”
mentioning
confidence: 99%
“…1 The expanded endonasal approach (EEA) and its modifications provide access to the anterior skull base, planum, sphenoid, sella, clivus, cervical spine, and infratemporal fossa via the two nostrils. [2][3][4][5][6][7][8][9] This approach enables endoscopic extradural and intradural tumor resection and skull base reconstruction in a single procedure.…”
Section: Introductionmentioning
confidence: 99%